Settlement of Village Apparatus Selection Dispute through the State Administrative Court - Jhoniansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In adjudicating disputes, judges at the State Administrative Court have the main duties of examining, adjudicating and resolving cases. In developments in society, the principle of active judges needs to be widely understood in order to provide justice. In this writing, the authors use normative law research methods (normative law research). After discussing the existing problems, it can be concluded that the State Administrative Court handles disputes that arise. state administration or state administration officials. Obstacles in the process of finalizing the selection through the State Administrative Court, the Plaintiff was not ready when he filed the lawsuit, Obstacles that generally occur at the Dismiss al Procedure stage of the State Administration when a summons has been made to the plaintiff and the defendant to be asked for an explanation by the chairman of the plaintiff's court is unable to attend and The regulations governing the selection of village officials are overlapping and lacking in detail. The State Administrative Dispute Settlement Process is carried out in two ways, namely through administrative efforts and through lawsuits to the State Administrative Court.